PENGATUR TEMPERATUR PADA DISPENSER BERBASIS ARDUINO MEGA 2560 - Yuspa Adi Putra; Kiki Prawiroredjo (Jetri : Jurnal Ilmiah Teknik Elektro, 2017)
A new innovative dispenser is proposed with the temperature control features to provide water to make coffee, tea, and milk as well as provide drinking water with hot, warm and cold temperatures. Resistance temperature detector PT-100 is used to sense the water temperature in the dispenser reservoir. The test results show that the water temperature range from this dispenser is 15 °C to 90 °C which fulfills the temperature requirements. The temperature difference between the LCD display and the thermometer is 2.7% for hot water, 4.5% for warm water, 13.3% for cold water, 1.66% for water to make coffee, 3.2% for water to make milk, and 3% for water to make tea. These errors occurred due to the component tolerances used.   Keywords: RTD PT-100, dispenser, temperature, LCD  ABSTRAK Dispenser dengan fitur pengaturan temperatur untuk membuat kopi, teh, dan susu serta dapat menyediakan air minum dengan temperatur panas, hangat dan dingin ini merupakan inovasi baru. Sensor yang digunakan adalah resistance temperatur detector PT-100 yang berfungsi untuk mendeteksi temperatur pada tampungan air dispenser. Dari hasil pengujian diperoleh range temperatur air pada dispenser ini adalah 15 °C sampai 90 °C sehingga sudah sesuai dengan kebutuhan. Perbedaan temperatur pada tampilan LCD terhadap termometer untuk air panas 2,7%, air hangat 4,5%, air dingin 13,3%, air untuk membuat kopi 1,66%, air untuk membuat susu 3,2%, dan air untuk membuat teh 3%. Kesalahan-kesalahan tersebut terjadi karena toleransi komponen yang digunakan. Kata kunci: RTD PT-100, dispenser, temperatur, LCD